Obstacles to use of patient expertise to improve care: a co-produced longitudinal study of the experiences of young people with sickle cell disease in non-specialist hospital settings. Issue 5 (19th October 2020) - Miles, Sam; Renedo, Alicia; Augustine, Cherelle; Ojeer, Patrick; Willis, Nordia; Marston, Cicely
ABSTRACT: Involving young people in their own healthcare is a global priority, yet we know little about how this might work in practice. In this paper, co-produced between academic researchers and people with lived experiences of sickle cell and its treatment, we examine how young people with sickle cell disease attempt to use their expertise in their own condition during emergency hospital admissions and through encounters with healthcare workers who are not sickle cell specialists. Our qualitative longitudinal research in England examined young people's experiences of hospital encounters via repeat and one-off interviews. We show that young people's expertise is sometimes undermined, including not being taken seriously when they report pain. They face barriers to care in non-specialist wards, particularly when they are alone with nobody to advocate for them. Although healthcare services use rhetoric that encourages young people to take control of their health and act as patient experts, in practice young people's expertise is routinely ignored. To improve health service quality, and meet the needs of young people, young people's own expertise must be better supported in routine interactions with healthcare providers.